Quick and cost-efficient A/D converter static characterization using low-precision testing signal. (April 2018) - Qin, Wei Wei; Sin, Sai-Weng; U, Seng-Pan; Martins, Rui Paulo
Abstract: The measurement of the analog-to-digital converter (ADC) output by exciting the signal generator with a high precision input signal allows the determination of ADC's static characteristics using a histogram-based approach. However, this method exhibits some limitations imposed by the input signal, including its high resolution and high linearity that are causes for concern when testing a high precision ADC. Recent research work has been trying to overcome such limitations. Nonetheless, it is necessary to discover a simple and low-cost method to measure the linearity of a high precision ADC through a low precision stimulus. This paper introduces a novel procedure that allows the relaxation of the requirements of the signal source for estimating ADC's linearity characteristics. The proposed method requires two sets of testing sources, being both ramp signals, one of low-precision and the other attenuated. Simulation and experimental results validate the proposed method in different ADCs.